Analysis of the Influence of Pentagon Fraud on FraudAcademics of Students of the S1 Accounting Study Program, Faculty of Economics and Business, University of Jambi - Khanifah, Nur; Sri Rahayu; Ratih Kusumastuti (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to determine the effect of pressure, opportunity, rationalization, ability, and arrogance on academic fraud behavior of students of the Accounting Study Program, Faculty of Economics and Business, University of Jambi. The data used in this study are primary data. The data collection method applied is quantitative using a questionnaire as a data collection tool. The population studied included Accounting students from 2020 to 2023, with a sampling technique using probability sampling through proportional random sampling, resulting in a total sample of 215 respondents. The results of this study indicate that the Pressure and Arrogance factors do not affect academic fraud of Accounting students at the University of Jambi, students feel no need to commit academic fraud because there is no pressure or main reason that supports committing fraud, besides that students are able to control their egos so that arrogance does not influence someone in committing fraud. However, in the Opportunity, Rationalization and Ability factors, they have an influence on academic fraud behavior, the greater the opportunity obtained, the greater the possibility of academic fraud behavior, in addition, undergraduate students of Accounting at Jambi University consider that fraud will not harm others, therefore rationalization is still one of the supporting factors in carrying out academic fraud, while in the ability factor, the higher the ability to cheat, the greater the possibility of academic fraud behavior occurring.